Application of Spatial Analysis to Eliminating Radicalism in Madrasah Schools - Afrizal Mansur; Jamaluddin Jamaluddin; Jumni Nelli; Muhammad Hanif; Nur Wahid; Haswir Haswir; Muhammad Marizal (Journal of Applied Engineering and Technological Science (JAETS), 2023)
The attack on the twin towers of the World Trade Center (WTC) on September 11, 2011 in New York, United States caused madrasas to be considered Islamic schools that gave birth to a radical generation. Madrasas' efforts to improve this negative image by improving the quality of education, especially 10 years after the incident, have succeeded in making Madrasas the schools of choice for students in Indonesia. This study focuses on analyzing the rise of Madrasah Tsanawiyah in the city of Pekanbaru, especially on students' mastery of knowledge for the last 4 years (2016, 2017, 2018 and 2019) by means of spatial analysis. The progress of science in Madrasas can be seen from the mapping of the value of knowledge, especially in the downtown area which is complete with various facilities and activity centers in Pekanbaru. The performance of some madrasas is almost the same as SMA in terms of mastery of knowledge. This study leads to an important analysis that the Pekanbaru madrasa as a Muslim-majority city has succeeded in making madrasas the main choice of parents to equip their children with religious and scientific education, which indirectly proves that madrasas do not provide space for the formation of radical Islamic generations, on the contrary. Madrasas have succeeded in forming a generation of Muslims who have good religious and scientific knowledge